PREVALENSI INFEKSI CACING TRICHURIS SUIS PADA BABI MUDA DI KOTA DENPASAR - Suratma, Nyoman Adi (Buletin Veteriner Udayana; Vol. 1 No. 2 Agustus 2009)
Three hundred faecal samples of suckling piglets from 4 districts in Denpasar Bali wereexamined to identify Trichuris infection by using flotation Method and then were analizedwith Descriptive analysis and Chi square analysis (Steel and Torrie, 1991).The prevalence of Trichuris suis infection in suckling piglets in Denpasar was 32,67 %(6166,87 ± 9827.5 EPG). The prevalence of Trichuris infection was significantly higher inpigs were kept on soil floor (52,70 %) than pigs were kept on concrete floor (26,11 %).The prsent study indicated that the infection ofTrichuris suis were prevalent in pig werekept on soil floor type.
Keywords: Trichuris suis, piglets, floor type